Central Nervous System Cryptococcosis in Patients With Sarcoidosis: Comparison With Non-sarcoidosis Patients and Review of Potential Pathophysiological Mechanisms - Prevel, Renaud; Guillotin, Vivien; Imbert, Sébastien; Blanco, Patrick; Delhaes, Laurence; Duffau, Pierre (Frontiers in Medicine, 2022)
Introduction Cryptococcus spp. infection of the central nervous system (CINS) is a devastating opportunistic infection that was historically described in patients with acquired immunodeficiency syndrome (AIDS). Cryptococcus spp. infections are also associated with sarcoidosis; the impairment of cell-mediated immunity and long-term corticosteroid therapy being evoked to explain this association. Nevertheless, this assertion is debated and the underlying pathophysiological mechanisms are still unknown. The aims of this study were (i) to describe the clinical and biological presentation, treatments, and outcomes of CINS patients with and without sarcoidosis and (ii) to review the pathophysiological evidence underlying this clinical association. Patients and Methods Every patient with positive cerebrospinal fluid (CSF) cryptococcal antigen testing, India ink preparation, and/or culture from January 2015 to December 2020 at a tertiary university hospital were included, and patients with sarcoidosis were compared with non-sarcoidosis patients. Quantitative variables are presented as mean ± SD and are compared using the Mann-Whitney Wilcoxon rank-sum test. Categorical variables are expressed as the number of patients (percentage) and compared using the χ2 or Fisher's tests. Results During the study period, 16 patients experienced CINS, of whom 5 (31%) were associated with sarcoidosis. CINS symptoms, biological, and CSF features were similar between CINS patients with and without sarcoidosis except regarding CD4 cells percentages and CD4/CD8 ratio that was higher in those with sarcoidosis (47 ± 12 vs. 22 ± 18, p = 0.02 and 2.24 ± 1.42 vs. 0.83 ± 1.10, p = 0.03, respectively). CINS patients with sarcoidosis had less often positive blood antigen testing than those without sarcoidosis (2/5 vs. 11/11, p = 0.02). CINS patients with and without sarcoidosis were treated with similar drugs, but patients with sarcoidosis had a shorter length of treatment. CD4 cell levels do not seem to explain the association between sarcoidosis and cryptococcosis. Conclusion Sarcoidosis was the most frequently associated condition with CINS in this study. CINS patients associated with sarcoidosis had overall similar clinical and biological presentation than CINS patients associated with other conditions but exhibited a lower rate of positive blood cryptococcal antigen testing and higher CD4/CD8 T cells ratio. Pathophysiological mechanisms underlying this association remain poorly understood but B-1 cell deficiency or lack of IgM could be a part of the explanation. Another plausible mechanism is the presence of anti-granulocyte-macrophage colony-stimulating factor (GM-CSF) antibodies in a subset of patients with sarcoidosis, which could impair macrophage phagocytic function. Further studies are strongly needed to better understand those mechanisms and to identify at-risk patients.